A Study on Literary Reading of University Readers: Temporal, Spatial, Interest Factors and the Moderation of Renewal Intention - Liu, Jie Xuan (Cipta Pustaka Nusantara, 2025)
This study investigates literary book borrowing dynamics at Nanjing Normal University (2016–2024), focusing on temporal-spatial-interest (TSI) factors and renewal intention’s moderation. Core data, segmented into 2016–2018, 2019–2021, and 2022–2024, includes gender, renewal status, monthly patterns, locations, and borrowing volumes across Chinese Library Classification (CLC) Category I subcategories. Principal Component Analysis derived TSI, SI, I, and S factors for regression, with renewal as a moderator and logarithmic total borrowing as the dependent variable. Structural Equation Modeling (SEM) explored latent structures, and ARIMA(1,0,0)(1,0,1) forecast trends. Findings show TSI exerts stronger influence than single/two-dimensional factors. TSI and renewal positively affect borrowing, peaking in 2019–2021, while renewal negatively moderates TSI’s impact. Subcategories under CLC Category I unveil distinct patterns between Chinese and world literature, mirroring the deepened interaction in literary reading interests between native and cross-regional literatures. SEM confirms a dual-factor framework, and ARIMA accurately predicts seasonal fluctuations. These insights advance literary engagement theory and inform library resource optimization.